Further evidence of hysteresis as a factor in the evaporation from soils - King, Larry G., author; Schleusener, Richard A., author (Colorado State University. Libraries, 1961)
Evaporation studies were conducted on a fine sand which was in contact with a water table and was subjected to diurnal cyclic atmospheric conditions. Previous studies under steady atmospheric conditions showed that an inverse relation between the rate of evaporation from soils and the rate of evaporation from a free-water surface occurred under certain conditions. These studies also showed that this inverse relationship was produced by decreased evaporativity as the depth to the water table was increased. A theoretical explanation of this phenomenon was presented on the basis of a hysteresis in the functional relation between permeability and saturation of soils. The data presented in the present paper show that this phenomenon also occurs under cyclic atmospheric conditions. The conclusion is that the inverse relationship could occur in soils under field conditions, and therefore it could be a significant cosideration in predicting evaporation from soils.
Atmospheric science technical paper no. 13 stamped on title page.
From the Journal of Geophysical Research, volume 66, no. 12, December 1961.
Keywords: Evaporation; Soil moisture -- Colorado -- Measurement; Hysteresis